Actions for the prevention and control of tobacco use in the school environment: An experience report (Research, Society and Development, 2021)
Objective: To report the educational activities carried out with adolescent students about the harmful effects of smoking and the importance of not starting and, when appropriate, stopping the habit of smoking. Method: This is an experience report of integrated activities in health, carried out by nursing students of a public higher education institution located in the Xingu Region, in November 2019. The educational actions were guided by the problematization methodology, with the practical operation of the Arco de Maguerez. Results: After initial contact with the target audience to verify their prior knowledge and needs on the subject, the students developed strategies to promote the educational moment that was operationalized through a video lesson designed for students about the components of cigarettes. In addition, a quiz was conducted through the plickers application where students could interact with academics, clarifying their doubts about the topic addressed. After that, two practical demonstrations were carried out in an open environment, with handcrafted simulators, developed by the students themselves, on the harmful effects of cigarette use on the lung. All activities had the consent of the school management and were developed under the supervision of a teacher. Final Considerations: The educational activities were extremely important, as they were delineated from the students' knowledge needs, solving their doubts about the theme. For undergraduates, the experience allowed the development of the integrated curriculum of the nursing course, in addition to qualifying the training process on the subject.